Insight into the wear properties of fiber fabric surface-enhanced composite under water lubrication - Chen, Jiazhen; Liang, Xingxin; Guo, Zhiwei; Li, Xuefei; Yuan, Chengqing (Tribology international, 2023)
Water-lubricated bearings are subject to abrasive wear, leading to performance degradation. Herein, the use of PTFE and UHMWPE fibers was investigated to improve surface tensile strength and explore wear mechanisms. Through finite element analysis and friction and wear experiments, it is hereby demonstrated that fiber reinforcement significantly improves surface tensile strength and reduces surface wear compared to non-reinforced materials, and the wear of the bronze plates is reduced as well. Meanwhile, fiber-reinforced composite materials suppress the development of wear in a certain amount of time and exhibit outstanding frictional performance. •Fabric effectively improves the surface tensile strength of the material.•Fabric acts as shock absorbers, reducing friction fluctuation and enhancing stability.•The incorporation of fabric mitigates abrasions and minimizes material removal.•Fabric altered the wear mechanism, effectively preventing the development of wear.